a^4 + b^4 + c^4 = (a^2 + b^2 + c^2)^2 - 2((ab)^2+(bc)^2+(ca)^2) = 1 - 2((ab)^2+(bc)^2+(ca)^2) (*)
Do a+b+c = 0 => (a+b+c)^2 = 0 => a^2 + b^2 + c^2 = -2(ab + bc + ca)
=> (a^2+b^2+c^2)^2 = 4(ab+bc+ca)^2 = 4.((ab)^2+(bc)^2+(ca)^2+2abc(a+b+c))
= 4.((ab)^2+(bc)^2+(ca)^2)
=> a^4 + b^4 + c^4 = 2.((ab)^2+(bc)^2+(ca)^2)
Thay lại vào (*) ta có a^4 + b^4 + c^4 = 1/2
(a+b+c)2=a2+b2+c2+2ac+2bc+2ab
=>02=1+2(ac+bc+ab)
=>ac+bc+ab=-1/2
=>(ac+bc+ab)2=a2b2+b2c2+a2c2+2a2bc+2b2ac+2c2ab
(ac+bc+ab)2=a2b2+b2c2+a2c2+2abc(a+b+c)
=>(-1/2)2=a2b2+b2c2+a2c2+2abc.0
=>a2b2+b2c2+a2c2=1/4
(a2+b2+c2)2=a4+b4+c4+2a2b2+2b2c2+2a2c2
(a2+b2+c2)2=a4+b4+c4+2(a2b2+b2c2+a2c2)
12=a4+b4+c4+2.1/4
1=a4+b4+c4.1/2
a4+b4+c4=1-1/2=1/2